The Relationship Between Parental Involvement in Educational Planning and Children's Emotional Wellbeing During Middle Childhood - Ima Siti Halimah; Asep Suryana; Nugraha Suharto (Papanda Publisher, 2026)
Emotional wellbeing during middle childhood significantly influences long-term developmental outcomes, yet the relationship between parental involvement in school-based educational planning and children's emotional wellbeing remains underexplored. This study examined the correlation between parental involvement in educational planning at school and emotional wellbeing among children in middle childhood. A quantitative correlational design was employed with 140 parents of elementary school children (ages 6-12 years) in Cicalengka Sub-district, Bandung Regency, Indonesia. Data were collected via validated questionnaires measuring parental involvement in educational planning (35 items, α = 0.955) and children's emotional wellbeing across three dimensions: hope for the future, sense of control, and self-worth (17 items, α = 0.864). Spearman's rank-order correlation analysis was conducted to assess the relationship between variables. A statistically significant positive correlation was found between parental involvement in educational planning and children's emotional wellbeing (rho = 0.537, p < 0.01), indicating a moderate-strength relationship. Active parental participation in school-based educational planning is meaningfully associated with enhanced emotional wellbeing in elementary school children. These findings suggest that institutional mechanisms facilitating parental engagement in educational decision-making may yield benefits extending beyond academic achievement to encompass psychological wellbeing, informing educational policy and family-school partnership initiatives.